PYRAZOLINES AS POTENT ANTITUBERCULAR AND CYTOTOXIC AGENTS - K, Ishwar Bhat; Kumar, Abhishek (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Pyrazolines are known to exhibit different biological and pharmacological properties such as anticancer, antibacterial, antifungal and antitubercular activities. Chalcones with an enone group between two aromatic rings exhibit remarkable pharmacological activities such as antiinflammatory, antibacterial, antitumor, antifungal, and antimalarial activity. A series of pyrazolines from chalcones have been synthesized and evaluated for antitubercular and cytotoxic activity studies. Methods: Chalcones [3-substituted phenyl-1-(p-tolyl)prop-2-en-1-one] were synthesized from various substituted aldehydes and 4-methyl acetophenone and cyclized into pyrazolines [5-substituted phenyl-3-(p-tolyl)-4,5-dihydro-1H-pyrazole] using hydrazine hydrate. Antitubercular and cytotoxic activity studies were carried out. Results: Antitubercular and cytotoxic activity studies of synthesized pyrazoline revealed that some compounds have showed promising activity. Conclusion: The observed results proved that pyrazolines are found to be interesting lead molecules for further synthesis as antitubercular and cytotoxic agents.